Lithium battery electrolyte and preparation method and application thereof

By using methyl trimethoxysilane, zinc trifluoromethanesulfonate and organic chelating agent in lithium battery electrolyte, the instability of lithium batteries in high temperature environments and the application challenges of aqueous zinc ion batteries are solved, and further development is achieved High cycle stability and efficiency enhance the safety and environmental friendliness of the battery.

CN119297394AInactive Publication Date: 2025-01-10YANGZHOU POLYTECHNIC INST
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411653344.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium battery electrolyte is unstable in high temperature environments, has safety hazards and is polluted to the environment, and the commercial application of water-based zinc ion batteries is limited by the dendrite growth, electrolyte decomposition and cathode dissolution of zinc anode.

Method used

Using lithium battery electrolyte including methyl trimethoxysilane, zinc trifluoromethanesulfonate and organic chelating agent, the zinc anode is stabilized by regulating the electrode/electrolyte interface, forming a protective solid electrolyte interface layer to improve the transmission of zinc ions Behavior and battery performance.

Benefits of technology

It significantly improves the cycle stability and efficiency of lithium batteries, extends the service life of lithium batteries, reduces the interaction between zinc ions and water, inhibits the formation of corrosion by-products, and enhances the high-temperature performance of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a lithium battery electrolyte and a preparation method and application thereof, in particular to a lithium battery electrolyte, which comprises a lithium salt, a mixed solvent and a diluent, the mixed solvent is composed of methyltrimethoxysilane, zinc trifluoromethanesulfonate and an organic chelating agent, the organic chelating agent is ammonium pyrrolidinedithiocarbamate, S, S ', S', S ', S', S ', S', S ', S', S ', S', S ', S', S ', S', S ', S', S ', S', S ', S', S ', S', S ', S', the solvent is one or more of N, N-dimethylformamide, N, N-dimethylformamide, S, S-ethylenediamine disuccinic acid, hydroxyethyl ethylenediamine triacetic acid and 2-bis (2-hydroxyethyl) amino-2-(hydroxymethyl)-1, 3-propylene glycol. The electrolyte additive can improve the cycling stability and efficiency of the aqueous zinc ion battery by regulating and controlling an electrode / electrolyte interface, stabilizing a zinc anode and improving the overall performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and more specifically, to a lithium battery electrolyte and a preparation method and application thereof. Background Art

[0002] As an emerging chemical energy source, lithium batteries have been widely used in people's production and life due to their excellent energy density, high operating voltage, long cycle life and environmental friendliness. It is not only widely used in portable electronic devices such as mobile phones, laptops, and cameras, but also considered to be an ideal power source for future electric and hybrid vehicles. This development trend has given lithium batteries a wide range of application prospects and huge economic benefits.

[0003] As a key component of ion transport, lithium battery electrolyte is usually composed of lithium salt and organic solvent. Its main function is to transfer ions between the positive and negative electrodes of lithium batteries, thereby ensuring that lithium-ion batteries have superior performance such as high voltage and high specific energy. The formula of the electrolyte generally contains high-purity organic solvents, electrolyte lithium salts and necessary additives, which are prepared by mixing them in a certain proportion under certain conditions. In traditional electrolytes, LiAlCl4+SO2 is an electrolyte that can achieve high cycle efficiency. The cycle efficiency of lithium metal electrodes in this electrolyte is close to 100%. However, since the electrolyte is highly corrosive, SO2 is volatile, it is easy to pollute the environment, and the preparation process requirements are high, so it is not suitable for practical applications. In addition, the LiAsF6 / DOL system electrolyte can also achieve high cycle efficiency at low current density. However, the solute LiAsF6 in this electrolyte is toxic, and the system is not stable enough, and it is easy to decompose when the temperature is too high. Especially in high temperature environments (>55°C), the stability of lithium battery electrolytes will drop sharply, and there are great safety hazards. Therefore, when selecting an electrolyte, it is necessary to weigh factors such as its cycle efficiency, toxicity, environmental friendliness, and stability to ensure that the lithium battery can exhibit good performance in actual use while meeting safety and environmental protection requirements.

[0004] The aging rate of lithium batteries is significantly affected by temperature. As the internal temperature of lithium batteries rises, the internal resistance of the battery increases, resulting in a decrease in battery capacity, which shortens the service life of lithium batteries. In extreme cases, excessively high temperatures may even cause explosions. Therefore, researchers have been actively exploring new high-temperature resistant lithium battery electrolytes to expand the operating temperature range of lithium batteries, enabling them to operate normally at conditions above 60°C, thereby expanding the application areas of lithium batteries.

[0005] As an emerging energy storage technology, aqueous zinc-ion batteries have attracted widespread attention for their low cost, high safety, good environmental sustainability and high energy density. However, problems such as zinc anode dendrite growth, electrolyte decomposition and cathode dissolution limit their commercial application. In order to overcome these challenges, the study of electrolyte additives has become a hot area. Electrolyte additives can improve the cycle stability and efficiency of aqueous zinc-ion batteries by regulating the electrode / electrolyte interface, stabilizing the zinc anode and improving the overall performance of the battery. Current research focuses on additives containing different functional groups, such as inorganic additives, organic additives, etc. These additives improve the performance of the battery by forming stable chemical bonds with the zinc anode, regulating the transport behavior of zinc ions, adjusting the solvation structure of zinc ions in the electrolyte and forming a protective solid electrolyte interface (SEI) layer. Summary of the invention

[0006] The present invention provides a lithium battery electrolyte and a preparation method and application thereof. The electrolyte additive can improve the cycle stability and efficiency of aqueous zinc ion batteries by regulating the electrode / electrolyte interface, stabilizing the zinc anode and improving the overall performance of the battery.

[0007] In a first aspect, the present invention provides a lithium battery electrolyte, comprising a lithium salt, a mixed solvent and a diluent, wherein the mixed solvent is composed of methyltrimethoxysilane, zinc trifluoromethanesulfonate and an organic chelating agent, and the organic chelating agent is one or more of ammonium pyrrolidinedithiocarbamate, S,S-ethylenediamine disuccinic acid, hydroxyethylethylenediaminetriacetic acid, and 2-bis(2-hydroxyethyl)amino-2-(hydroxymethyl)-1,3-propanediol.

[0008] Preferably, the lithium salt is one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorophosphate and lithium bis(fluorosulfonyl)imide, and the concentration of the lithium salt in the electrolyte is 1-1.5 mol / L.

[0009] Preferably, the lithium salt is one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorophosphate and lithium bis(fluorosulfonyl)imide, and the concentration of the lithium salt in the electrolyte is 1.2-1.5 mol / L.

[0010] Preferably, the diluent is any one or more of anisole, fluorobenzene, trifluorobenzene 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 2,2,2-trifluoroethyl-1,1,2,3,3,3-hexafluoropropyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, fluorobenzene and 1,2-difluorobenzene.

[0011] Preferably, the mass fraction of the methyltrimethoxysilane is 2%-8%, the mass fraction of the zinc trifluoromethanesulfonate is 5%-12%, and the mass fraction of the organic chelating agent is 20%-30%.

[0012] In a second aspect, the present invention provides a method for preparing a lithium battery electrolyte, comprising the following steps: (1) removing water from methyltrimethoxysilane, zinc trifluoromethanesulfonate and an organic chelating agent; (2) Drying the lithium salt; (3) Methyltrimethoxysilane, zinc trifluoromethanesulfonate and an organic chelating agent are mixed in proportion, and lithium salt and a diluent are added and mixed until they are completely dissolved to obtain the lithium battery electrolyte.

[0013] Preferably, the temperature of the lithium salt drying treatment is 80-95° C., and the drying time is 12-16 hours.

[0014] In a third aspect, the present invention provides an application of a lithium battery electrolyte in a lithium ion battery.

[0015] Preferably, the positive electrode material of the lithium-ion battery is one of lithium iron phosphate, lithium cobalt oxide, ternary, and lithium-rich manganese-based positive electrode materials, and the negative electrode material is a lithium sheet.

[0016] In summary, the present invention has the following beneficial effects: 1. The zinc trifluoromethanesulfonate of the present invention can make Zn 2+ The interaction with water molecules is reduced, so that the [Zn(H2O)6] 2+ The solvation shell is limited, which ultimately shows higher capacity and better cycling stability; 2. The organic chelating agent of the present invention can react with Zn 2+ The formation of a stable complex will increase the nucleation overpotential, and the hydration degree of zinc ions in the electrolyte will decrease, which can change the molecular weight of water contained in the inner Helmholtz plane, and the formation of corrosion by-products and hydrogen evolution reaction will be inhibited to a certain extent; 3. The additives of the present invention are methyltrimethoxysilane, zinc trifluoromethanesulfonate and an organic chelating agent. The additives improve the performance of the battery by forming a stable chemical bond with the zinc anode, regulating the transport behavior of zinc ions, adjusting the solvation structure of zinc ions in the electrolyte and forming a protective solid electrolyte interface layer.

[0017] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not intended to limit the scope of protection of the present invention. DETAILED DESCRIPTION

[0018] The present invention is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the reactions are carried out according to conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources. Example

[0019] Example 1 A method for preparing a lithium battery electrolyte comprises the following steps: (1) lithium hexafluorophosphate is selected as the lithium salt, S,S-ethylenediamine disuccinic acid is selected as the organic chelating agent, methyltrimethoxysilane and zinc trifluoromethanesulfonate are selected as the organic solvent, and 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE) is selected as the diluent; (2) In a glove box with a humidity of less than 0.01 ppm, molecular sieves were added with medium-methyl trimethoxysilane, zinc trifluoromethanesulfonate and S,S-ethylenediamine disuccinic acid to remove water, and the mixture was allowed to stand for 12 hours; lithium hexafluorophosphate was placed in the glove box and then dried at 100° C.; (3) 8% methyltrimethoxysilane, 12% zinc trifluoromethanesulfonate, 30% S,S-ethylenediamine disuccinic acid, and 30% lithium hexafluorophosphate were weighed respectively according to their mass percentages so that the total concentration of lithium salt in the electrolyte was 1.5 mol / L, and the mixture was thoroughly mixed until completely dissolved to obtain an electrolyte.

[0020] Example 2 A method for preparing a lithium battery electrolyte comprises the following steps: (1) selecting lithium hexafluorophosphate as the lithium salt, selecting ammonium pyrrolidine dithiocarbamate as the organic chelating agent, selecting methyltrimethoxysilane and zinc trifluoromethanesulfonate as the organic solvents, and selecting 2,2,2-trifluoroethyl-1,1,2,3,3,3-hexafluoropropyl ether (TTE) as the diluent; (2) In a glove box with a humidity of less than 0.01 ppm, molecular sieves were added to methyl trimethoxysilane, zinc trifluoromethanesulfonate and ammonium pyrrolidine dithiocarbamate to remove water, and the mixture was allowed to stand for 12 hours; lithium hexafluorophosphate was placed in the glove box and then dried at 100° C.; (3) Weigh 6% methyltrimethoxysilane, 10% zinc trifluoromethanesulfonate, 30% ammonium pyrrolidinedithiocarbamate, and 40% lithium hexafluorophosphate respectively according to their mass percentages so that the total concentration of lithium salt in the electrolyte is 1.5 mol / L, and mix them thoroughly until they are completely dissolved to obtain an electrolyte.

[0021] Example 3 A method for preparing a lithium battery electrolyte comprises the following steps: (1) lithium hexafluorophosphate is selected as the lithium salt, hydroxyethylethylenediaminetriacetic acid is selected as the organic chelating agent, methyltrimethoxysilane and zinc trifluoromethanesulfonate are selected as the organic solvent, and 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE) is selected as the diluent; (2) In a glove box with a humidity of less than 0.01 ppm, molecular sieves were added with medium-methyl trimethoxysilane, zinc trifluoromethanesulfonate and hydroxyethylethylenediaminetriacetic acid to remove water, and the mixture was allowed to stand for 12 hours; lithium hexafluorophosphate was placed in the glove box and then dried at 100° C.; (3) Weigh 5% methyltrimethoxysilane, 8% zinc trifluoromethanesulfonate, 30% hydroxyethylethylenediaminetriacetic acid, and 30% lithium hexafluorophosphate respectively according to their mass percentages so that the total concentration of lithium salt in the electrolyte is 1.5 mol / L, and mix them thoroughly until they are completely dissolved to obtain an electrolyte.

[0022] Example 4 A method for preparing a lithium battery electrolyte comprises the following steps: (1) lithium hexafluorophosphate is selected as the lithium salt, 2-bis(2-hydroxyethyl)amino-2-(hydroxymethyl)-1,3-propanediol is selected as the organic chelating agent, methyltrimethoxysilane and zinc trifluoromethanesulfonate are selected as the organic solvent, and 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE) is selected as the diluent; (2) In a glove box with a humidity of less than 0.01 ppm, molecular sieves were added to medium-methyl trimethoxysilane, zinc trifluoromethanesulfonate, and 2-bis(2-hydroxyethyl)amino-2-(hydroxymethyl)-1,3-propanediol to remove water, and the mixture was allowed to stand for 12 hours; lithium hexafluorophosphate was placed in the glove box and then dried at 100°C; (3) 8% methyltrimethoxysilane, 11% zinc trifluoromethanesulfonate, 30% 2-bis(2-hydroxyethyl)amino-2-(hydroxymethyl)-1,3-propanediol, and 30% lithium hexafluorophosphate were weighed respectively according to their mass percentages so that the total concentration of lithium salt in the electrolyte was 1.5 mol / L. The electrolyte was obtained after the mixture was thoroughly mixed until it was completely dissolved.

[0023] Comparative Example Comparative Example 1 Prepare commercial electrolytes as follows: (1) In a glove box with a humidity of less than 0.01 ppm, ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate were measured in a volume ratio of 1:1:1 to prepare an organic solvent; (2) Add lithium salt LiPF6 to the organic solvent of step (1) so that the concentration of the lithium salt in the electrolyte is 1 mol / L, and stir thoroughly to obtain a commercial electrolyte.

[0024] Comparative Example 2 Prepare commercial electrolytes as follows: (1) In a glove box with a humidity of less than 0.01 ppm, ethylene carbonate and diethyl carbonate were measured in a volume ratio of 3:7 to prepare an organic solvent; (2) Add lithium salt LiPF6 to the organic solvent of step (1) so that the concentration of the lithium salt in the electrolyte is 1 mol / L, and stir thoroughly to obtain a commercial electrolyte.

[0025] Performance Test: The electrolytes prepared in Examples 1-4, Comparative Examples 1 and 2 were respectively injected into 2025 button battery shells, with an injection volume of 70 μL. The positive electrode was a commercial NCM811 electrode sheet, and the negative electrode was lithium metal. A full battery was prepared for testing. The voltage range was 2.7V-4.3V, the ambient temperature was 60°C, and the activation was performed at 0.1C charge and discharge. The cycle test was performed at 1C charge and discharge. The number of cycles was 100-500 times, and the discharge specific capacity was 200-350 mAh / g. The results of charging and discharging the NCM811 ternary lithium battery of the electrolyte prepared in Example 1 under the conditions of 2.7-4.3V, 60°C high temperature, and 1C charge and discharge were 50-200 mAh / g. The rate performance of the NCM811 ternary lithium battery prepared by the electrolyte in Example 1 and Comparative Example 1 was tested at 2.7-4.3V, 60°C high temperature and different rates, and the result was 120-200mAh / g; the coulombic efficiency of the Li-Cu battery prepared by the electrolyte in Example 1 and Comparative Example 1 was tested, and the result was that the number of cycles was 250-1000 and the coulombic efficiency was 70-95%.

[0026] The electrolyte prepared in Example 1 has excellent cycle performance. The ternary lithium battery made therefrom has a discharge specific capacity of more than 200 mAh / g at high temperature (60°C), a coulombic efficiency of more than 99.5%, and a discharge specific capacity retention rate of 87% after 250 cycles; the electrolyte prepared in Example 1 also has excellent rate performance, with a capacity of up to 155 mAh / g at a rate of 10C.

[0027] The above is only an exemplary embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A lithium battery electrolyte, characterized in that: The invention comprises a lithium salt, a mixed solvent and a diluent. The mixed solvent is composed of methyltrimethoxysilane, zinc trifluoromethanesulfonate and an organic chelating agent. The organic chelating agent is one or more of ammonium pyrrolidinedithiocarbamate, S,S-ethylenediamine disuccinic acid, hydroxyethylethylenediaminetriacetic acid and 2-bis(2-hydroxyethyl)amino-2-(hydroxymethyl)-1,3-propanediol.

2. The lithium battery electrolyte according to claim 1, characterized in that: The lithium salt is one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorophosphate and lithium bis(fluorosulfonyl)imide, and the concentration of the lithium salt in the electrolyte is 1-1.5 mol / L.

3. The lithium battery electrolyte according to claim 1, characterized in that: The diluent is any one or more of anisole, fluorobenzene, trifluorobenzene, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 2,2,2-trifluoroethyl-1,1,2,3,3,3-hexafluoropropyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, fluorobenzene and 1,2-difluorobenzene.

4. The lithium battery electrolyte according to claim 1, characterized in that: The mass fraction of the methyltrimethoxysilane is 2%-8%, the mass fraction of the zinc trifluoromethanesulfonate is 5%-12%, and the mass fraction of the organic chelating agent is 20%-30%.

5. The method for preparing the lithium battery electrolyte according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) removing water from methyltrimethoxysilane, zinc trifluoromethanesulfonate and an organic chelating agent; (2) Drying the lithium salt; (3) Methyltrimethoxysilane, zinc trifluoromethanesulfonate and an organic chelating agent are mixed in proportion, and lithium salt and a diluent are added, and mixed until they are completely dissolved to obtain the lithium battery electrolyte.

6. The method for preparing a lithium battery electrolyte according to claim 5, characterized in that: The temperature of the lithium salt drying treatment is 80-95° C., and the drying time is 12-16 hours.

7. Use of the lithium battery electrolyte according to any one of claims 1 to 6 in lithium ion batteries.

8. The use according to claim 7, characterized in that: The positive electrode material of the lithium-ion battery is one of lithium iron phosphate, lithium cobalt oxide, ternary, and lithium-rich manganese-based positive electrode materials, and the negative electrode material is a lithium sheet.

Citation Information

Cited By

  • Micro additive for absorbing and purifying CO2, preparation method and application

    CN121222219A